2012
DOI: 10.3109/09638288.2012.697249
|View full text |Cite
|
Sign up to set email alerts
|

Multi-professional and multi-dimensional group education – a key to action in elderly persons

Abstract: Elderly persons who are independent may have difficulty accepting information about preventing risks to health. However, group education with a multi-professional approach may be a successful model for achieving an exchange of knowledge, which may possibly empower the participants, give them role models, the opportunity to learn from each other and a sense of sharing problems with people in similar circumstances.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 46 publications
2
28
0
Order By: Relevance
“…Previous studies (Behm, Ivanoff, et al, 2013; Behm, Zidén, et al, 2013) have found that there may be psychological barriers to assimilating information early when that information is not perceived to apply to oneself, or is difficult to accept as it may not apply at the present time. Our results support this argument, as participants’ experiences of their own needs or those of others were important for decisions about taking action now or deferring action.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies (Behm, Ivanoff, et al, 2013; Behm, Zidén, et al, 2013) have found that there may be psychological barriers to assimilating information early when that information is not perceived to apply to oneself, or is difficult to accept as it may not apply at the present time. Our results support this argument, as participants’ experiences of their own needs or those of others were important for decisions about taking action now or deferring action.…”
Section: Discussionmentioning
confidence: 99%
“…This may be due to fear or insecurity concerning expected negative changes that may threaten health during ageing. A recent focus group study reported that older people who live in the present thought that it was difficult to assimilate information that they did not consider to be of current interest [41]. The fact that older people live in the present and find it difficult to assimilate the information might also explain the finding mentioned above.…”
Section: Discussionmentioning
confidence: 99%
“…An interview study of participants in PHV showed that experiencing that someone was interested, listened, and took time to talk to them made them feel valuable, and that they were still important persons in society (Behm et al, 2013a). Thus, the participants were empowered, and their self-esteem was strengthened (Behm, Ziden, Duner, Falk, & Dahlin-Ivanoff, 2013b;Behm et al, 2013a). It is well known that the stronger the participants' beliefs in their ability, that is, self-efficacy, the more likely they are to engage in or take actions (Bandura, Freeman, & Lightsey, 1999).…”
Section: Discussionmentioning
confidence: 99%